2016
DOI: 10.1038/mtm.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a hybrid β-hexosaminidase subunit capable of forming stable homodimers that hydrolyze GM2 ganglioside in vivo

Abstract: Tay-Sachs or Sandhoff disease result from mutations in either the evolutionarily related HEXA or HEXB genes encoding respectively, the α- or β-subunits of β-hexosaminidase A (HexA). Of the three Hex isozymes, only HexA can interact with its cofactor, the GM2 activator protein (GM2AP), and hydrolyze GM2 ganglioside. A major impediment to establishing gene or enzyme replacement therapy based on HexA is the need to synthesize both subunits. Thus, we combined the critical features of both α- and β-subunits into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 52 publications
2
57
0
1
Order By: Relevance
“…The HEXM gene, which encodes the modified Hex a-subunit variant, l, overcomes this challenge because the Hex l-subunit can form a stable homodimer, HexM, which functionally replaces the HexA heterodimer. 28 Overexpression of HexM has been shown to result in its enhanced secretion, and secreted HexM is taken up by other deficient cells through plasma membrane mannose 6-phosphate receptors. In addition, unlike HexA, both active sites in the HexM homodimer can potentially bind the G M2 AP-G M2 complex and hydrolyze G M2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEXM gene, which encodes the modified Hex a-subunit variant, l, overcomes this challenge because the Hex l-subunit can form a stable homodimer, HexM, which functionally replaces the HexA heterodimer. 28 Overexpression of HexM has been shown to result in its enhanced secretion, and secreted HexM is taken up by other deficient cells through plasma membrane mannose 6-phosphate receptors. In addition, unlike HexA, both active sites in the HexM homodimer can potentially bind the G M2 AP-G M2 complex and hydrolyze G M2 .…”
Section: Discussionmentioning
confidence: 99%
“…Likely, the encouraging results reported by Matsuoka and colleagues are attributable to restoration of HexB-like activity that takes advantage of the alternative sialidase pathway in mice. As an alternative approach to develop a hybrid subunit, Tropak and colleagues 28 designed a modified asubunit incorporating both the unique b-subunit sequences required to form a stable, HexB-like, homodimer and those sequences needed for the homodimer to interact with the G M2 AP-G M2 complex. The a-active site was retained in order to facilitate the hydrolysis of negatively charged substrates, for example, G M2 .…”
Section: Introductionmentioning
confidence: 99%
“…Jakkolwiek nie ma jeszcze zastosowania w TSD. Celem badań jest określenie drogi jaką enzym zastępczy mógłby pokonać barierę krew-mózg [14,15]. Terapia metodą ograniczenia substratu (SRT, substrate reduction therapy) ma na celu ograniczenie produkcji cząstek, których rozkład jest upośledzony.…”
Section: Ryc 2 3 Zaniki Korowe Móżdżku (Mr Mózgu Przekrój Poprzeczunclassified
“…As part of the initial characterization of HexM, Tropak et al 28 who used the same mice for short-term analysis of G M2 ganglioside, reported that these neonatal mice injected with scAAV9.47/ HEXM vector had a significant reduction in the storage of the G M2 ganglioside compared with the scAAV9.47/GFP and PBS control mice, but there was still a significant amount of G M2 ganglioside stored in the scAAV9.47/HEXM-injected mice compared with the heterozygous control mice. However, at the long-term terminal endpoint, the G M2 ganglioside levels in scAAV9.47/HEXMinjected mice at 36-49 weeks of age were not different from those in untreated mice at 12-16 weeks of age (Fig.…”
Section: Decrease In G M2 Ganglioside Accumulation In the Aav947/hexmentioning
confidence: 99%
“…This HexM enzyme has been shown to be capable of catabolizing the G M2 ganglioside substrate in association with the human GM2AP. 28 The gene for this new l-subunit, HEXM, is *1.6 kb, and, combined with short regulatory sequences, is able to fit within the scAAV packaging constraints. 29 The current study evaluates the therapeutic effects of systemic delivery of scAAV9.47/HEXM vector in the neonatal SD mouse model.…”
Section: Introductionmentioning
confidence: 99%